2016
DOI: 10.1007/jhep03(2016)044
|View full text |Cite
|
Sign up to set email alerts
|

Constraining conformal field theories with a higher spin symmetry in d > 3 dimensions

Abstract: We study unitary conformal field theories with a unique stress tensor and at least one higher-spin conserved current in d > 3 dimensions. We prove that every such theory contains an infinite number of higher-spin conserved currents of arbitrarily high spin, and that Ward identities generated by the conserved charges of these currents imply that the correlators of the stress tensor and the conserved currents of the theory must coincide with one of the following three possibilities: a) a theory of n free bosons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
152
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 47 publications
4
152
0
Order By: Relevance
“…form (1.4) with n > 2 imply that the correlators of the energy-momentum tensor coincide with those of the free theory [5,6]. The classification of unitary representations in (1.2) reveals that there are possible conserved currents beyond the symmetric ones described above.…”
Section: Jhep02(2018)131mentioning
confidence: 95%
See 3 more Smart Citations
“…form (1.4) with n > 2 imply that the correlators of the energy-momentum tensor coincide with those of the free theory [5,6]. The classification of unitary representations in (1.2) reveals that there are possible conserved currents beyond the symmetric ones described above.…”
Section: Jhep02(2018)131mentioning
confidence: 95%
“…When k = 7, the bound may be saturated by the free field operator F F ∂F demonstrating that the result (1.10) is optimal. When k = 6, the bound cannot be saturated by free fields and it is unclear whether operators of spin (6,1) exist in the range 6 ≤ ∆ < 13/2. Given the form of our (k, 0) and (k, 1) results, it is tempting to conjecture a general formula for the gap in the spectrum of anomalous dimensions of general Lorentz representations implied by the average null energy condition.…”
Section: Calculations and Conjecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it was shown in [44] that if a 3-dimensional CFT which is unitary, obeys the cluster decomposition axiom and has a (unique) Lorentz covariant stress-tensor plus at least one higher-spin current, then this theory is either a CFT of free scalars or free spinors. This was generalised to arbitrary dimensions in [45,46] 3 , where the authors showed that this result holds in dimensions d 3, up to the additional possibility of a free CFT of ( d−2…”
mentioning
confidence: 81%